2020
DOI: 10.1007/s42977-020-00032-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of future land use changes on hydrologic ecosystem services: a case study from the Zala catchment, Hungary

Abstract: Maintaining and, where possible, improving the ecological status of our water resources are of particular importance for the future. So, one of the main drivers of landscape design must be to protect our waters. In this study, we carried out an evaluation of four hydrologic ecosystem services (HES) in the Zala River catchment area, the largest tributary of Lake Balaton (more than half of the lake’s surface inflow comes from the Zala River), Hungary. The lake has great ecological, economic and social importance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Several ES studies concluded that alternative land use systems -focusing more on climate adaptation and regulating services -could lead to higher social benefits than present conditions [10][11][12]. This is in line with empirical evidence and with policy recommendations as well: both emphasize the importance of water retention and wetland restoration efforts (e.g., [13][14][15]).…”
Section: Introductionsupporting
confidence: 53%
“…Several ES studies concluded that alternative land use systems -focusing more on climate adaptation and regulating services -could lead to higher social benefits than present conditions [10][11][12]. This is in line with empirical evidence and with policy recommendations as well: both emphasize the importance of water retention and wetland restoration efforts (e.g., [13][14][15]).…”
Section: Introductionsupporting
confidence: 53%
“…Scenario analyses might shed light on anticipated changes in ES value as well as adopting values from other regions to a hypothetical situation, similar to the benefit transfer technique widely used for economic valuation of ES (e.g. Reynaud and Lanzanova 2017 ; Decsi et al 2020 ; Vermaat et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the greater the difference in exported loads, the greater the contribution of the nutrient retention service. Other studies that used the NDR model also observed negative effects on water purification services with the reduction of natural areas [82][83][84][85].…”
Section: Analysis Of the Effects Of Lulc Changes On Baseflow And The ...mentioning
confidence: 93%